Increased Silicon Acquisition in Bananas Colonized by Rhizophagus irregularis MUCL 41833 Reduces the Incidence of Pseudocercospora fijiensis - Gbongue, Louis-Raymond; Lalaymia, Ismahen; Zeze, Adolphe; Delvaux, Bruno; Declerck, Stéphane (Frontiers in Plant Science, 2019)
This work aimed to test the hypothesis that the combination of arbuscular mycorrhizal fungi (AMF) and accumulation of silicon (Si) in banana plants via its uptake and transport by the fungus reduces the incidence of Black Leaf Steak Disease (BLSD) caused by Pseudocercospora fijiensis. Methods: A pot experiment was conducted to compare BLSD symptoms on leaves of banana plants colonized or not by the AMF Rhizophagus irregularis MUCL 41833 and exposed or not to Si added to the growth substrate. Results: A marked increase in plant growth parameters (i.e. pseudostem diameter and height, leaf surface area, shoot, root and total dry weight) as well as accumulation of Si, P and Ca were noticed in the AMF-colonized banana plants in presence as well as in absence of Si added to the growth substrate. Similarly Si addition to the substrate increased plant growth parameters. Leave symptoms caused by the pathogen were observed in all the treatments but were reduced in presence of AMF as well as in presence of Si added to the growth substrate. The more drastic reduction was noticed in the AMF-colonized plants with Si added to the growth substrate. The Severity Index as well as Area Under Disease Progress Curve were considerably decreased both at 21 (~ 48% and 48% respectively) and 35 days (~ 21% and ~ 32% respectively) after inoculation of the pathogen as compared with non AMF-colonized plants in absence of Si added to the substrate. Conclusion: Our findings revealed that AMF-colonized banana plants grown in a substrate supplemented with Si were less impacted by P. fijiensis than non-colonized plants grown without Si added to the growth substrate. The combination of AMF-colonized banana plants (during the weaning phase or in vitro) with the application of Si to soil seems thus a thoughtful option to mitigate the impact of BLSD in bananas, although such strategy needs first to be evaluated under field conditions to appraise its real potential.